Effects of wearing removable dentures and aging on palatal mucosa blood flow by laser doppler - Ayepa Alain Kouadio; Jordana Fabienne; Assem Soueidan; Christelle Volteau; N'goran Justin Koffi; Kouadio Benjamin Djérédou; Pierre Le Bars (Wolters Kluwer Medknow Publications, 2022)
Aim: The purpose of this work is to analyze the effects of removable dental prostheses and aging on blood microcirculation in the palatal mucosa. Settings and Design: Blood flow was measured in two groups using the Laser Doppler Flowmeter at three specific anatomical sites: Retro incisive papilla, medial raphe, and Schroeder area. Materials and Methods: Group 1 included young, healthy dentulous individuals (mean age: 23 ± 3 years), and Group 2 contained elderly edentulous individuals (mean age: 62 ± 11.69 years). For Group 1, measurements were taken in a single session; for Group 2, the measurements were taken in two sessions: The first just before the prosthetic load (E1) and again 1 week after new dentures were provider (E2). Statistical Analysis Used: Statistical analyses were performed using SAS software, Version 9.4 of the SAS System for Windows, Copyright © 2017 SAS Institute Inc. (Cary, NC, USA). A P < 0.05 was classified as statistically significant. Results: Measurements of blood flow of the palatal mucosa showed that the healthy young dentulous participants had significantly lower perfusion unit values than the elderly edentulous participants at all three anatomical sites (P < 0.05). For Group 2, the comparisons between the measurements taken before (E1) and after (E2) new dentures were provided showed no significant differences. Conclusion: Our results indicate that the process of aging significantly modifies the blood flow of the palatal mucosa while wearing removable dental prostheses does not modify the blood flow of the palatal mucosa in a 1week period. These results are not influenced by systemic pathology (e.g., diabetes, cardiovascular diseases) or smoking.